2014
DOI: 10.4274/npa.y6751
|View full text |Cite
|
Sign up to set email alerts
|

Ergenlerde İnternet Kullanımı ile Uyku Problemleri Arasındaki İlişki

Abstract: Problematic sleep habits and sleep problems were found to be more frequent in adolescents with a higher IAS total score. Health care providers must be aware of the possible negative impact of excessive and uncontrolled internet use on adolescents' sleep habits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 26 publications
1
22
0
2
Order By: Relevance
“…It is plausible that excessive Internet use/online social networking inhibits adolescents’ sleeping patterns. Addicts might need more time to fall asleep and may have shorter sleep duration than non-addicts, contributing to a higher risk of insomnia ( Ekinci et al., 2014 ; Harbard, Allen, Trinder, & Bei, 2016 ; Nalwa & Anand, 2003 ). Furthermore, excessive Internet use may significantly disturb adolescents’ sleep–wake schedules, which may lead to irregular sleep patterns and insomnia ( Chen & Gau, 2016 ; Lam, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is plausible that excessive Internet use/online social networking inhibits adolescents’ sleeping patterns. Addicts might need more time to fall asleep and may have shorter sleep duration than non-addicts, contributing to a higher risk of insomnia ( Ekinci et al., 2014 ; Harbard, Allen, Trinder, & Bei, 2016 ; Nalwa & Anand, 2003 ). Furthermore, excessive Internet use may significantly disturb adolescents’ sleep–wake schedules, which may lead to irregular sleep patterns and insomnia ( Chen & Gau, 2016 ; Lam, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…IA and OSNA compete with off-line activities including time that could be used for sleeping, and hence potentially cause insomnia. Excessive Internet use among adolescents often occurs at night ( Primack, Swanier, Georgiopoulos, Land, & Fine, 2009 ), and adolescents with a higher IA score reported getting to bed later, requiring more time to fall asleep, and disrupting their sleep–wake schedule (i.e., increased number of awakening at night) than those with lower IA score ( Ekinci, Celik, Savas, & Toros, 2014 ; Van den Bulck, 2004 ). Adolescents with OSNA are at a high risk of insomnia ( Hanprathet, Manwong, Khumsri, Yingyeun, & Phanasathit, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays in many societies, adolescents are known to use the internet when they indeed are expected to sleep (38)(39)(40), and they delay their sleep hours as accessing the internet with devices including tablet, smartphones and computer which lead suppression of melatonin release (14,41,42). In the studies, which were conducted for the purpose of analysing the relationship between adolescents' internet use and sleep habits, the frequency of sleep problems in adolescents who spent longer time in internet increased (15,35), felt lack of sleep (43,44) and slept fewer hours in nights (13,19,38,45) as similar to our study result. Internet use also affected adolescents to fall asleep durations (15,45).…”
Section: Discussionmentioning
confidence: 99%
“…Internet usage especially increases toward adolescence period from pre-adolescence period (12). Previous studies showed that adolescents who spend more time on the internet delayed their sleeping hours, slept more late on weekdays and weekends, took less sleep during the day and had more fatigue during the day (13)(14)(15)(16). Therefore, internet usage increases the intellectual, emotional and physiological triggers and affects negatively their sleep quality due to the factors such as more exposure to bright light (17).…”
Section: Introductionmentioning
confidence: 99%
“…[ 19 20 ] Internet addicts lose their sleep due to being online and forget their nutrition and physical activity. [ 21 22 ] Reports of deaths due to heart attack during use of the internet, which can be due to physical disorders such as insomnia, and lack of exercise. [ 23 ] On the other hand, anonymous nature of the internet makes people say things or do things on the internet that they do not in a normal position.…”
Section: Introductionmentioning
confidence: 99%